Political and Legal Keys to Adoption in Republican and Augustan Age - Castán, Santiago (Gerión. Revista de Historia Antigua, 2020)
Adoption, an old institution of family law and inheritance, was a regular instrument used for political purposes by the republican nobility and the first emperors. The article focuses on the political keys of this institute as a new mechanism in politics of those times, studying specifically the testamentary adoption of Cayo Octavio, and those made later by him in order to ensure the political succession of the Principate.
Keywords: Adoptio; Adrogatio; Caesar; Testamentary adoption; Augustus; Political succession in the Principate